Vaccines for the prevention of meningococcal capsular group B disease: What have we recently learned?. Issue 1 (2nd January 2016) - Findlow, Jamie
Abstract : Meningococcal disease remains a feared and devastating cause of sepsis and meningitis. Disease incidence is highest among infants and children although a significant burden of disease is experienced by adolescents, young adults and those with specific risk-factors. Prevention of disease against capsular groups A, C, W and Y; 4 of the 5 most pathogenic groups is achievable using capsular polysaccharide vaccines. It has only recently been possible to provide protection against capsular group B (MenB) strains following the licensure of a 4 component group B vaccine (4CMenB) in Europe in 2013. Following licensure, 4CMenB has been used in specific at-risk groups and in response to outbreaks of MenB disease. The largest outbreak interventions have been in students at 2 universities in the United States and for all individuals aged 2 months to 20 years of age in Quebec, Canada. The vaccine was recommended in February 2014 for implementation into the UK infant schedule at 2, 4 and 12 months of age, although it has taken over 12 months to resolve procurement discussions to enable implementation. The UK recommendation incorporates prophylactic paracetamol with infant doses when 4CMenB is administered concomitantly with routine vaccines. This is based on recent data demonstrating the ability of paracetamol to reduce fever rates to background levels without impacting immunogenicity. Post-implementation surveillance will be important to provide vaccine efficacy data as this was not possible to determine in pre-licensure studies due to the relative infrequency of MenB cases.